2018
DOI: 10.1186/s40608-018-0214-4
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and fathers’ media parenting practices associated with young children’s screen-time: a cross-sectional study

Abstract: BackgroundA major contributor to the growing obesity crisis is screen based sedentary behaviour among young children. Media parenting practices may be an important determinant of children’s screen time, however published research exploring the influence of parenting practices on children’s screen time has mainly focused on children’s television use and the parenting practices of the mother. This study examined children’s use of mobile media devices (as well as television use) and included the role of fathers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 24 publications
5
93
1
5
Order By: Relevance
“…In general, parents thought that by using mediation strategies, such as ensuring their children viewed appropriate content, setting time limits for their children’s use of devices, and continuously monitoring their children while they used a device, they could ensure that their children primarily benefited from using mobile screen devices. Although research exploring parental mediation strategies in the context of mobile screen technologies is still limited, the forms of mediation practices parents in our study described using are consistent with those found in the limited but growing body of research on mobile screen technologies and young children (e.g., Beyens and Beullens, 2017 ; Tang et al, 2018 ; Domoff et al, 2019 ), and those found in the extensive research on TV, which have been primarily been conducted among middle-class, White parents ( Nathanson, 1999 , 2001 ; Warren, 2003 ; Collier et al, 2016 ; Piotrowski, 2017 ). Furthermore, the diverse Latine parents in this study described being cognizant of the important role they play in mediating their children’s use of mobile screen devices.…”
Section: Discussionsupporting
confidence: 83%
“…In general, parents thought that by using mediation strategies, such as ensuring their children viewed appropriate content, setting time limits for their children’s use of devices, and continuously monitoring their children while they used a device, they could ensure that their children primarily benefited from using mobile screen devices. Although research exploring parental mediation strategies in the context of mobile screen technologies is still limited, the forms of mediation practices parents in our study described using are consistent with those found in the limited but growing body of research on mobile screen technologies and young children (e.g., Beyens and Beullens, 2017 ; Tang et al, 2018 ; Domoff et al, 2019 ), and those found in the extensive research on TV, which have been primarily been conducted among middle-class, White parents ( Nathanson, 1999 , 2001 ; Warren, 2003 ; Collier et al, 2016 ; Piotrowski, 2017 ). Furthermore, the diverse Latine parents in this study described being cognizant of the important role they play in mediating their children’s use of mobile screen devices.…”
Section: Discussionsupporting
confidence: 83%
“…SBs are implicated in a variety of serious physical health problems-primarily in the context of obesity-and psychopathological conditions. Given the increasing prevalence of severe obesity and time spent gaming (Phan et al 2019), and the increasing recognition of the role of screenbased activities as a major contributor to the obesity epidemic (Sánchez-Oliva et al 2018;Tang et al 2018), the need to address prevention measures and evaluate the efficacy of respective interventions is timely. The purpose of the present review was to identify interventions on screenbased SBs and to elucidate the role of recreational screen behaviours and the way these are targeted within the interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they present later and have a delayed diagnosis. Another explanation for the increased risk of a delayed diagnosis with increased initial screen time is children’s screen time practices are often a reflection of parental screen time practices ( 21 ). Increased use of screen devices by parents can impact parent-child interaction and quality time ( 22 ).…”
Section: Discussionmentioning
confidence: 99%